(untitled) (INNOTEC, 2018)
Beekeeping is in development in Uruguay, where more than 90% of the production is sold for export. The aim of this work was to investigate the relation between the botanical origin and honey conductivity. Conductivity is an indirect measurement of the ash, and from the nutritional point of view, it is an indicator of the mineral composition of the honey, which is an important supplement of human diet. Honeycombs frames were studied from diﬀerent geographic areas from Uruguay. The honey was extracted by a press at laboratory and fltered by a synthetic cloth. Colour, moisture, electrical conductivity, and pollen content were analysed. The darker honeys presented higher conductivity values. The higher electrical conductivity observed was from native bush, Eucalyptus spp. forest and Honeydew. Uruguayan native bush honey is unique in the world and has typical ﬂavour. Moreover, this type of honey has higher levels of conductivity that makes it a good source of minerals.